2019
DOI: 10.19113/sdufenbed.566570
|View full text |Cite
|
Sign up to set email alerts
|

Hızlı Soğutma Sürecinde Dörtlü Zr48Cu36Ag8Al8 İri Hacimli Metalik Camının Atomik Yapısının Gelişimi

Abstract: Özet: Çalışmamızda Zr48Cu36Al8Ag8 dörtlü alaşımının atomik yapısı ve cam oluşturma süreci moleküler dinamik simülasyon ile gömülü atom metodu kullanılarak araştırıldı. Cam geçiş sürecini ve sıcaklığa bağlı atomik yapı gelişimini araştırmak için ortalama hacim-sıcaklık eğrisi, çiftler dağılım fonksiyonu (PDF) ve çift analiz metodu kullanıldı. 300 K'de hesaplanan toplam PDF, g(r), daha önce rapor edilen deneysel g(r) ile iyi bir uyum sağlamaktadır. Öte yandan ortalama hacim-sıcaklık grafiğinden yararlanılarak be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
(37 reference statements)
0
0
0
1
Order By: Relevance
“…Therefore, in this study, EAM potential was chosen to simulate the rapid solidification process of BMGs by MD. Although some previous reports have suggested that the results obtained by this EAM potential cannot explain the interaction between Al [23][24][25][26] and Ag [24,25] in the system very well, for the Zr-Cu-Al-Ag quaternary system of this study, there is currently no reported potential functions available, and different potential functions cannot be combined arbitrarily. Therefore, this EAM [20] potential is almost the only choice for analyzing the Zr-Cu-Al-Ag quaternary metallic glasses system.…”
Section: Molecular Dynamic Simulationsmentioning
confidence: 79%
“…Therefore, in this study, EAM potential was chosen to simulate the rapid solidification process of BMGs by MD. Although some previous reports have suggested that the results obtained by this EAM potential cannot explain the interaction between Al [23][24][25][26] and Ag [24,25] in the system very well, for the Zr-Cu-Al-Ag quaternary system of this study, there is currently no reported potential functions available, and different potential functions cannot be combined arbitrarily. Therefore, this EAM [20] potential is almost the only choice for analyzing the Zr-Cu-Al-Ag quaternary metallic glasses system.…”
Section: Molecular Dynamic Simulationsmentioning
confidence: 79%
“…CuTi nanotellerin mekanik özellikleri üzerine boyut ve germe oranı gibi iki dış değişkenin etkilerini araştırmak için Large-Scale Atomic-molecular Massively Parallel (LAMMPS) [27] açık kaynak kodu kullanılmıştır. Bütün benzetimlerde Cu-Cu, Cu-Ti ve Ti-Ti atom çiftleri arasındaki etkileşmeleri tanımlamak için daha önce metalik sistemlerin kırılma, kusur ve tane sınırları gibi özelliklerini açıklamakta [23,[28][29][30] başarılı sonuçlar verdiği rapor edilen Zhou ve ark. [31] tarafından geliştirilen GAM potansiyeli kullanılmıştır.…”
Section: Materyal Ve Metotunclassified